Something wild : [large type] a novel - Halperin, Hanna (Thorndike Press, a part of Gale, a Cengage Company, 2021)
"One weekend, sisters Tanya and Nessa Bloom pause their respective adult lives and travel to the Boston suburbs to help their mother pack up and move out of their childhood home. For the first time since they were teenagers sharing a bunk bed over a decade ago, they find themselves in the place where long-kept secrets were born, where jealousy, comfort, anger, forgiveness, and repulsion coexist with the fiercest love and loyalty. What they don't expect is for their visit to expose a new, horrifying truth: their mother, Lorraine, is in a violent relationship. As Tanya urges Lorraine to get a restraining order, Nessa struggles to reconcile her fondness for their stepfather with his capacity for brutality. Their differing responses to the abuse bring up the sisters' shared secret--a traumatic, unspoken experience from their adolescence has shaped their lives, their sense of selves, and their relationship with each other and the men in their life. In the midst of this family crisis, they have no choice but to reckon with the past and face each other in the present, in the hope that there's a way out of the violence so deeply ingrained in the Bloom family. Told in alternating perspectives that deftly interweave past and present, Something Wild is a magnetic, unflinching portrait of the bond between sisters, as well as a psychologically acute exploration of the legacy of divorce, the ways trauma reverberates over generations, and how it might be possible to overcome the past"--